USM ENGINEERING GRADUATES ARE HIGHLY SOUGHT AFTER BY INDUSTRY - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
NIBONG TEBAL, March 2015 The support given especially by the industries for programmes organised by the Universiti Sains Malaysia (USM) Engineering students has proven that the students are acknowledged to have reputable skills and abilities.